Differential Change in Retina Structure and Function in Children and Adolescents with Drusens of the Optic Nerve Disk - A. G. Shchuko; D. Yu. Samsonov; S. I. Zhukova; T. N. Iureva; I. M. Mikhalevich; A. V. Grigorieva; Yu. S. Samsonova (Oftalʹmologiâ)
The first histological and clinical description of the optic nerve drusens was given in the 19th century. Then authors considered drusens as congenital pathologies, and a study of 1999 showed that drusen is not the primary pathology, but the dysplasia of the optic nerve disk and its circulation predisposes to the formation of drusen. Central vision in patients with drusens of the optic nerve disc is reduced rarely, and their diagnosis is reduced to ascertaining of the fact of having drusen without taking into account the structural and functional changes in the visual system.Purpose of the work: to identify the pattern of changes in visual functions in children and adolescents with druses of the optic nerve disk, the development and addition of classification criteria.Patients and methods. 45 children with drusens were examined, a comprehensive analysis of the visual system included a standard ophthalmological examination, a comprehensive study of visual system with ultrasound scanning, OCT and OCTA, standard automated and pulsarperimetry.Based on the results of the cluster analysis, a graph of the distribution of patients into three groups (control group and two clinical groups) was constructed, and the structural and functional state of the visual system was analyzed. Drusens in children in the second group we marked as “peripheral”, and in the third — “central”. The carried out researches have shown, that the revealed disturbances are more expressed in the third clinical group. All this determines the need to complement the clinical classification of drusens and their separation depending on the location relative to the vessels of the optic nerve disk to the central and peripheral. The compression effect of drusen is accompanied with changes in the volume of the optic nerve disc, a violation of retinal hemodynamics, damage to the neuroglia and ganglion cells, which allows treating this pathology as a progressive neuroopticopathy, and the revealed dependence of changes on the localization of druses requires supplementing the existing classification.